Propuesta de implementación de buenas prácticas de manufactura (BPM) en la industria láctea la americana, ubicada en la parroquia Mulalo, cantón Latacunga, provincia Cotopaxi - Quilumba Macato, Luz Belén (2014)
Historically the Good Manufacturing Practices ( GMP ) arise as a response or reaction to serious events ( sometimes fatal ) , related to the lack of safety , purity and efficacy of food. This new regulation includes aspects : GMP , development and implementation of standard operating procedures for safety, performance standards for pathogen reduction and that all processing facilities develop and implement an early warning system aimed at improving products. This research was developed by phases , where a was applied a survey , the staff of the lacteal La American company to determine the level of knowledge of Good Manufacturing Practices , in order to determine precisely the need for a manual dairy company La Americana….